Effect of PIONER (Oxytocin Massage with Electromagnetic Stimulation) on Breast Milk Production: A Repeated-Measures Intervention Study Among Postpartum Mothers - Rosida Hi. Saraha; Rabiah Umanailo; Darwis Durahim; Fahrul Islam (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Breast milk production is regulated by prolactin and oxytocin, and oxytocin massage is known to facilitate milk ejection. To address limitations of manual stimulation, an electromagnetic-assisted oxytocin massage device (PIONER) was developed to support postpartum mothers in improving breast milk flow. This study aimed to evaluate the effectiveness of the PIONER device in improving breast milk production indicators among postpartum breastfeeding mothers. Methods: A quasi-experimental repeated-measures design was conducted involving 10 postpartum breastfeeding mothers selected using purposive sampling from three community health centers in Ternate City. PIONER-assisted oxytocin massage was administered on days 1, 3, 5, 7, and 9, twice daily for 10 minutes. Breast milk adequacy indicators urination frequency, defecation frequency, breastfeeding frequency, infant sleep duration, and infant weight were measured on days 2, 4, 6, 8, and 10. Data were analyzed using repeated-measures ANOVA (Greenhouse–Geisser correction) with a significance level of ? = 0.05. Results: Significant time-based differences were observed for urination frequency (F = 13.500, p = 0.005), defecation frequency (F = 25.839, p < 0.001), and infant weight (F = 45.375, p < 0.001). No significant changes occurred in breastfeeding frequency or sleep duration. Confidence intervals could not be calculated because raw standard errors were not available. Conclusion: PIONER effectively improved indicators of breast milk production, particularly urinary and fecal output and infant weight gain, with no adverse effects observed during the study. Larger controlled studies are recommended to strengthen generalizability.